2017
DOI: 10.1016/j.ijhm.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Price determinants of sharing economy based accommodation rental: A study of listings from 33 cities on Airbnb.com

Abstract: The advent of the "sharing economy" challenges not only the business of hotel industry but also the theories and models based on the conventional hotel industry. A key dimension of the hospitality industry is pricing. The aim of this study is to identify the price determinants of sharing economy based accommodation offers in the digital marketplace. Specifically, a sample of 180,533 accommodation rental offers in 33 cities listed on Airbnb.com is investigated using ordinary least squares and quantile regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
381
9
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(476 citation statements)
references
References 53 publications
29
381
9
17
Order By: Relevance
“…In Figure 5a, significant negative correlations between number of reviews and price exist primarily in west Metro Nashville (districts 18,[20][21][22][23][24][25]34). The negative correlations indicate that the more reviews the listing has, the lower the price, which is inconsistent with previous studies [11]. In Metro Nashville, guests tend to choose lower price listings, and then Airbnb hosts would be more likely to lower their price in order to attract more guests.…”
Section: Gwr Estimationmentioning
confidence: 69%
See 2 more Smart Citations
“…In Figure 5a, significant negative correlations between number of reviews and price exist primarily in west Metro Nashville (districts 18,[20][21][22][23][24][25]34). The negative correlations indicate that the more reviews the listing has, the lower the price, which is inconsistent with previous studies [11]. In Metro Nashville, guests tend to choose lower price listings, and then Airbnb hosts would be more likely to lower their price in order to attract more guests.…”
Section: Gwr Estimationmentioning
confidence: 69%
“…For example, Ikkala and Lampinen [10] reported that the reputation of Airbnb listings is correlated with their price. Using Airbnb listings information from 33 cities, Wang and Nicolau [11] identified five price-determinant categories of Airbnb listings, including host attributes, site and property attributes, amenities and services, rental rules, and online review ratings. Li et al [30] proved the effects of distance to the nearest landmark, the impact of facility, and nearest landmark popularity on Airbnb listing prices.…”
Section: Airbnb Listing Pricementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the determinants of prices on Airbnb are discussed to some extent. Factors such as host attributes, site and property attributes, amenities and services, rental rules, and online review ratings are stated to have a significant relationship with listings' prices on Airbnb platform (Li, Pan, Yang, & Guo, 2016;Wang & Nicolau, 2017).…”
Section: Airbnb: An Emerging Platform Of Sharing Economy Based Accommmentioning
confidence: 99%
“…For example, Airbnb and Uber have catalyzed a vibrant SE discourse, participated in by the media, information communication technology industries, venture capitalists, entrepreneurs and grassroots activists [4]. Although with a common expectation that the sharing economy niche will disrupt multiple regimes by radically decentralizing economic activity, in the five years since the emergence of a sharing economy concept rooted in contrasting and contradictory ways.…”
Section: Introductionmentioning
confidence: 99%